Achievement of guideline recommended diabetes treatment targets and health habits in people with self-reported diabetes in India (ICMR-INDIAB-13): a national cross-sectional study. Issue 6 (June 2022) - Anjana, Ranjit Mohan; Unnikrishnan, Ranjit; Deepa, Mohan; Venkatesan, Ulagamathesan; Pradeepa, Rajendra; Joshi, Shashank; Saboo, Banshi; Das, Ashok Kumar; Bajaj, Sarita; Bhansali, Anil; Madhu, Sri Venkata; Dhandhania, Vinay Kumar; et al.
Summary: Background: There is little information on comprehensive diabetes care comprising glycaemic, lipid, and blood pressure control in India; therefore, we aimed to assess the achievement of treatment targets among adults with self-reported diabetes. Methods: The Indian Council of Medical Research (ICMR)-India Diabetes (INDIAB) study is a cross-sectional, population-based survey of adults aged 20 years or older in all 30 states and union territories of India. We used a stratified multistage sampling design, sampling states in a phased manner, and selected villages in rural areas and census enumeration blocks in urban areas. We used a three-level stratification method on the basis of geography, population size, and socioeconomic status for each state. For the outcome assessment, good glycaemic control was defined as HbA1c of less than 7·0% (A), blood pressure control was defined as less than 140/90 mm Hg (B), and the LDL cholesterol target was defined as less than 100 mg/dL (C). ABC control was defined as the proportion of individuals meeting glycaemic, blood pressure, and LDL cholesterol targets together. We also performed multiple logistic regression to assess the factors influencing achievement of diabetes treatment targets. Findings: Between Oct 18, 2008, and Dec 17, 2020, 113 043 individuals (33 537 from urban areas and 79 506 from rural areas) participated in the ICMR-INDIAB study. For this analysis, 5789 adults (2633 in urban areas and 3156 in rural areas) with self-reported diabetes were included in the study population. The median age was 56·1 years (IQR 55·7–56·5). Overall, 1748 (weighted proportion 36·3%, 95% CI 34·7–37·9) of 4834 people with diabetes achieved good glycaemic control, 2819 (weighted proportion 48·8%, 47·2–50·3) of 5698 achieved blood pressure control, and 2043 (weighted proportion 41·5%, 39·9–43·1) of 4886 achieved good LDL cholesterol control. Only 419 (weighted proportion 7·7%) of 5297 individuals with self-reported diabetes achieved all three ABC targets, with significant heterogeneity between regions and states. Higher education, male sex, rural residence, and shorter duration of diabetes (<10 years) were associated with better achievement of combined ABC targets. Only 951 (weighted proportion 16·7%) of the study population and 227 (weighted proportion 36·9%) of those on insulin reported using self-monitoring of blood glucose. Interpretation: Achievement of treatment targets and adoption of healthy behaviours remains suboptimal in India. Our results can help governments to adopt policies that prioritise improvement of diabetes care delivery and surveillance in India. Funding: Indian Council of Medical Research and Department of Health Research, Ministry of Health and Family Welfare.